Clinical Features That Evoke the Concept of Disinhibition in Tourette Syndrome - Kurvits, Lille; Martino, Davide; Ganos, Christos (Frontiers in Psychiatry, 2020)
The capacity to efficiently control motor output, by either refraining from prepotent actions or disengaging from ongoing motor behaviors, is necessary for our ability to thrive in a stimulus-rich and socially complex environment. Failure to engage in successful inhibitory motor control could lead to aberrant behaviors typified by an excess of motor performance. In tic disorders and Tourette syndrome (TS), which is the most common tic disorder encountered in clinics, surplus motor output is rarely the only relevant clinical sign. Indeed, a range of abnormal behaviors is often encountered, which are historically viewed as “disinhibition phenomena”. Here, we present the different clinical features of TS from distinct categorical domains (motor, sensory, complex behavioral), which evoke the concept of disinhibition and discuss their associations. We also present evidence for their consideration as phenomena of inhibitory dysfunction and provide an overview of studies on TS pathophysiology, which support this view. We then critically dissect the concept of disinhibition in TS and illuminate other salient aspects, which should be considered in a unitary pathophysiological approach. We briefly touch upon the dangers of oversimplification and emphasize the necessity of conceptual diversity in the scientific exploration of TS, from disinhibition and beyond.